2017
DOI: 10.1590/1980-5918.030.002.ao15
|View full text |Cite
|
Sign up to set email alerts
|

Effects of functional resistance training on muscle strength and musculoskeletal discomfort

Abstract: Introduction: Functional resistance training (FRT) is becoming increasingly popular to improve physical fitness of practitioners, however, yet there are gaps in knowledge about effectiveness of FRT in relation conventional resistance training (CRT) in several ambits, as musculoskeletal complaints. Objective: Compare the effect of FRT and CRT in the musculoskeletal discomfort and magnitude of gain in muscle strength in healthy women. Methods: 52 women was divided into three groups, FRT (n = 15; 22 ± 2.35 years)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
4
0
1
Order By: Relevance
“…At the same time, it has been revealed that the optimal training combination of muscle strength and cardiorespiratory fitness is more effective in improving the athletic performance of the young athletes than single-mode training effects (Gäbler, Prieske, Hortobágyi, & Granacher, 2018). However, there are data proving that functional training does not have significant advantages in improving muscular fitness and strength characteristics compared to the traditional methods of training effects (Cassemiro et al, 2017;Weiss et al, 2010). For a significant increase in the results both types of training effects are important: traditional and functional (Beckham, & Harper, 2010).…”
Section: Karol Görner -----------------------------------------------mentioning
confidence: 99%
“…At the same time, it has been revealed that the optimal training combination of muscle strength and cardiorespiratory fitness is more effective in improving the athletic performance of the young athletes than single-mode training effects (Gäbler, Prieske, Hortobágyi, & Granacher, 2018). However, there are data proving that functional training does not have significant advantages in improving muscular fitness and strength characteristics compared to the traditional methods of training effects (Cassemiro et al, 2017;Weiss et al, 2010). For a significant increase in the results both types of training effects are important: traditional and functional (Beckham, & Harper, 2010).…”
Section: Karol Görner -----------------------------------------------mentioning
confidence: 99%
“…In the FTG, the patients reported high fatigue during functional exercises, this may be justified by the fact that functional exercises simultaneously work several body structures, promoting balance between the upper and lower parts of the limbs and trunk, and consequently better neuromuscular activation and higher musculoskeletal adaptation, 38 as well as simulating routine activities, 18 which the patients have difficulty performing due to the characteristics of the disease. 39 In addition, the functional exercises were formulated by the most difficult activities to execute, reported by patients with COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Se resaltan todavía otros hallazgos, como en el estudio de Cassemiro et al (2017) Cabe resaltar, que además de los métodos de entrenamiento utilizados EFZA y EF en este estudio, que ya están descritos ampliamente en la literatura demostrando su eficacia en la mejora en las múltiples variables de la salud (Cassemiro et al, 2017, Guedes et al, 2016, Heubel et al, 2018, De Resende et al, 2019a, también fue usado de forma innovadora, la inclusión del método EJA, en el cual (Borba et al, 2013a;2013b;, presentaron el EJA como alternativa en la protección contra caídas en mujeres en edad avanzada, mostrando mejoras en el desempeño del equilibrio, fuerza muscular, mantenimiento de la densidad mineral ósea y la calidad de vida comparado al GC.…”
Section: Discussionunclassified